Studies on Root Architecture in Elephant Foot Yam (Amorphophallus paeoniifolius (Dennst.) Nicolson) - S., Sunitha; Ravi, Velumani; V., Ramesh (JOURNAL OF ROOT CROPS, 2020)
Experiments were conducted at ICAR-CTCRI during 2016 and 2017 to study the rooting pattern of elephant foot yam, variety Gajendra under drip irrigation and rainfed conditions, by growing the crop in semi permanent cement tanks and periodical uprooting. The root system, emerging from the newly developing corms, was shallow growing to a maximum depth of 30-40 cm, but spread horizontally upto 1.2 m.The pattern of rooting was more or less similar during both the seasons. Number of roots, length and root biomass increased gradually from sprouting, and reached maximum at full canopy development stage or 3 MAP. These parameters declined with corm bulking and reached minimum at crop senescence. Both number of roots, root dry matter and depth of rooting were less under limited soil moisture. However, rainfed crop retained more number of lengthy roots, and biomass towards later stages than irrigated crop